Strategi dan Model Pengembangan Objek Wisata Air Panas di Desa Tombasian Kecamatan Kawangkoan Barat Kabupaten Minahasa - Telly Hetty Isje Kondoj; Vesti L Sambeka (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
Tourism development is sought to be developed in the context of economic improvement, sustainable development and technological development. Geographically, each region has different characteristics with their own uniqueness and advantages. Natural resources that are owned with all its contents, land in all its forms and the sea with all its contents. This potential can be utilized optimally through tourism. Natural resources owned with all their contents and existing potential will be utilized for development purposes. That potential can be an asset through the tourism sector. One of the attractions that attracts the attention of both domestic and foreign tourists is the hot springs in Tombasian Bawah Village. Tombasian Bawah Village is one of the villages in Kawangkoan Barat District, Minahasa Regency, where in general the people work as farmers and craftsmen on stilt houses. Furthermore, the data that has been collected is analyzed by descriptive analysis using the SWOT analysis method and breaking it down internally and externally. The stages of the research were field observations by collecting data at the physical location, conducting interviews with the government of tourist attraction locations with village programs and district governments related to the development of tourism objects, specifically hot water in the village of Tombasian Bawah and visitors to obtain data. The results of the study show that the Hot Spring Tourism Object Development Strategy is adequate which can be applied by developing tourism on holidays and other holidays. And the model is community based. The development of this hot spring tourism object can be done by diversifying tourism objects and modifying the system so that tourists can travel easily and pleasantly. The results of this research are the proceding/Sentrinov output targets and reports. KEY WORDS : Strategy, Development, Tourism Object, Hot Water, Tombasian Bawah, Style